ANALYSIS OF THE USE OF ROLE PLAY TO IMPROVE SPEAKING SKILL AT PRIMER AÑO DE BACHILLERATO, AT UNIDAD EDUCATIVA “MIGUEL ÁNGEL LEÓN PONTÓN” IN THE CITY OF RIOBAMBA, CHIMBORAZO PROVINCE, DURING THE ACADEMIC PERIOD 2018-2019. - Camacho Freire, Gissela Katherine (2019)
The objective of the study was to analyze the use of Role Play to improve the speaking skill of students coursing the Primer Año de Bachillerato, at Unidad Educativa “Miguel Ángel León Pontón” in the city of Riobamba, Chimborazo Province, during the academic period 2018-2019. The study was proposed since after some observations, it was evidenced that it is very difficult for students to initiate, maintain and conclude a conversation in the classroom by using English. The study frames into the qualitative approach, in this regard the ethnographic method was used. For the data collection process, it was used an observation which was carried out during some classes and a survey that was applied to the teacher. The instruments were constructed bearing in mind the theoretical basis presented in the theoretical framework. The results demonstrate that the most important factors to accurately apply Role Play in speaking activities were neglected in the pre, while and post stages and so the results are not the desired. It is suggested to take pedagogical courses, since the weaknesses detected in the application of role plays did not affect only to the speaking development but to the learning goals in general and also to keep a better relationship between theory and practice; it will help improve the teacher’s professional performance and students’ learning goals.